Effects of Different Aging Treatments on Functional Components and Flavor Substances of Chrysanthemum Rice Wine - Wei GAO; Huaining YIN; Aiyuan WANG; Baokun DING; Yunhao ZHANG; Ling XIONG; Xinyue FENG; Maobin CHEN; Yu ZHANG (Shipin gongye ke-ji)
Three methods including ultrasound (US), microwave (MW), and a combination of ultrasound and microwave (SW), were used to treat rice wine and chrysanthemum rice wine for 3 and 7 d respectively. The basic physicochemical indicators, antioxidant activity, flavor substances, and sensory evaluation of wine samples were analyzed to explore the effects of different aging treatments on the functional components and aromatic profile of chrysanthemum rice wine. The results showed that after 7 d of microwave treatment, chrysanthemum rice wine exhibited the highest reducing sugar content of 112.92±7.39 mg/mL. The total acid content of the samples increased under three different aging methods. Notably, 7 d of ultrasound treatment significantly increased the total acid content in chrysanthemum rice wine (P<0.05). After 3~7 d of microwave treatment, the polyphenol content of both rice wine and chrysanthemum rice wine increased, while the flavonoid content enhanced under ultrasound treatment conditions. Antioxidant activity assessments demonstrated that, in contrast to the control group, the DPPH radical scavenging capacity of chrysanthemum rice wine decreased from 60.49%±0.04% to 19.69%±1.78% after microwave treatment for 7d (P<0.05). Following a 3 d of combined ultrasound and microwave treatment, the ABTS+ radical scavenging rate of chrysanthemum rice wine rose, while it decreased under other treatments. All three methods improved the total antioxidant capacity of chrysanthemum rice wine, with microwave treatment for 7 d yielding the highest FRAP value. During the aging process, the free radical scavenging rate and total antioxidant capacity of chrysanthemum rice wine were stronger than those of rice wine. GC-MS analysis indicated that the types and relative contents of flavor substances in chrysanthemum rice wine decreased under three different aging treatments, but isobutanol increased under different conditions. After 3 d of combined ultrasonic microwave treatment, the relative content of ethyl palmitate increased significantly. The relative content of 3-hydroxy-2-butanone increased under three treatments of chrysanthemum rice wine. Ultrasound treatment for 3 d had the best retention effect on the flavor compounds in chrysanthemum rice wine, preserving 34 flavor substances. The sensory evaluation results showed that after 3 d of combined ultrasound and microwave treatment, chrysanthemum rice wine possessed a harmonious taste and exhibited a floral honey aroma. This suggests that appropriate aging techniques can enrich the flavor compounds, balance the nutritional constituents, and improve the taste of chrysanthemum rice wine.